2020
DOI: 10.3390/ijerph17041173
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Eudaimonic Well-Being in Mental Health Care Organizations: The Role of Servant Leadership and Workplace Civility Climate

Abstract: Demanding and complex work within mental health care organizations places employee well-being at risk and raises the question of how we can positively influence the psychological well-being and functioning of these employees. This study explores the role of servant leadership and workplace civility climate in shaping eudaimonic well-being among 312 employees in a Dutch mental health care organization. The findings showed that servant leadership had a stronger relationship with eudaimonic well-being when workpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 87 publications
1
21
0
3
Order By: Relevance
“…Third, this study challenges the common notion that servant leaders display empathy and heal their followers' emotional sufferings, thus, helping to decrease depression [46]. The results from the literature review revealed that servant leadership is positively associated with all its positive outcome variables, such as engagement, job satisfaction, and organizational commitment [49,50]. However, although this study did not hypothesize servant leadership to be related to depersonalization and physical health, the study results demonstrated that servant leadership is not associated with either depersonalization or physical health.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Third, this study challenges the common notion that servant leaders display empathy and heal their followers' emotional sufferings, thus, helping to decrease depression [46]. The results from the literature review revealed that servant leadership is positively associated with all its positive outcome variables, such as engagement, job satisfaction, and organizational commitment [49,50]. However, although this study did not hypothesize servant leadership to be related to depersonalization and physical health, the study results demonstrated that servant leadership is not associated with either depersonalization or physical health.…”
Section: Discussionmentioning
confidence: 69%
“…If schools aspire to seek a trade-off and gain a mutual benefit of both hindrance stress and teachers' well-being, it is recommended that educational authorities recruit and train school principals and other administrators in servant leadership practices, with a particular focus on empowering their teachers in a way to help them to achieve sustainable development. These newly empowered teachers, trained in servant leadership principles, should begin to influence and encourage positive moral actions [50]. Finally, there is a spillover effect of depersonalization on the teacher's well-being.…”
Section: Discussionmentioning
confidence: 99%
“…En general, los autores recientes coinciden en la importancia de estudiar la felicidad en el trabajo y el desempeño laboral, a nivel individual y grupal, y en revisar nuevas medidas desde la perspectiva eudaimónica (Bartels et al,2019;Der Kinderen et al, 2020;Erazo Muñoz & Riaño-Casallas, 2021). De acuerdo con los clúster presentados, en el clúster 1, la tendencia económica e internacional de la felicidad, representa el 12.78 % del total de los artículos de la red, y está compuesta por 306 nodos y 536 aristas; los temas principales giran en torno a la Relación entre felicidad en el trabajo felicidad internacional, es decir, la medición de esta según el país (Saz-Gil et al 2019;Blanchflower & Oswald, 2011;Rodríguez-Pose & Von Berlepsch, 2014), cómo afectan los rasgos de las personas, asociados con su nacionalidad, a su felicidad (Steel & Ones, 2002), cómo afectan los factores socioeconómicos y socioculturales la felicidad en los países y qué aportes pueden tomar los economistas de la investigación de la felicidad, con el fin de tenerlos en cuenta para proponer políticas económicas (Easterlin, 1995;Frey & Stutzer, 2002), todos desde la perspectiva del bienestar subjetivo y la satisfacción laboral.…”
Section: Discussionunclassified
“…El tema central de trabajo corresponde a enfoques emergentes en el estudio de la relación entre felicidad en el trabajo y desempeño laboral, enmarcado en tres líneas: la primera, la felicidad desde la eudaimonía, partiendo de las propuestas de Huta & Ryan (2010), Ryan & Deci (2001) y Ryff & Keyes (1995). Solo hasta el 2016 se empezaron a realizar estudios donde se relacionan la felicidad eudaimónica en el trabajo y el desempeño laboral (Der Kinderen et al, 2020;Kożusznik et al, 2019;Turban & Yan, 2016;Villajos et al, 2019); estos coinciden en que la investigación en el campo ha estado concentrada en la felicidad desde el hedonismo o la felicidad en general, y no específicamente en el trabajo (Bartels et al, 2019), y que es necesario construir una escala de felicidad en el trabajo y medir su relación con el desempeño laboral. La segunda línea emergente está relacionada con los diferentes patrones de relaciones entre el rendimiento y la felicidad, infeliz-improductivo, feliz-productivo, feliz-improductivo e infelizproductivo (Ayala et al, 2017;Peiró et al, 2019); de hecho, Ayala et al (2017) encontraron que casi el 15 % de los empleados tenían un patrón ampliamente ignorado por estudios previos (por ejemplo, infeliz productivo).…”
Section: Discussionunclassified
See 1 more Smart Citation